Revitalisasi Komunitas Pembelajaran dengan Lesson Study dalam Meningkatkan Kualitas Pembelajaran - Widiyanto Widiyanto (INOPENDAS: Jurnal Ilmiah Kependidikan, 2018)
This article aims to produce a design concept in forming Learning Community using Lesson Study to improve Learning Quality, therefore this article is a concept framework (Theorical Framework) Strategy to Build Learning Quality using Lesson Study. Study Sources are theoretical and research findings using theoretical analysis. The main objectives can be achieved by finding the basic objectives: (1) identifying the Lesson Study Implementation, (2) identifying the barriers to the implementation of the Lesson Study; (3) Identify effective learning communities for improving learning quality, and (4) develop a revitalization design of Lesson Study implementation to establish an effective learning community in improving learning. The result of the study found that there are still obstacles in implementing Lesson Study because of the problem of perception, time, support, funding, and social culture of students. About a good learning community will be overwhelmed if there are regular meetings, stakeholder support, adequacy of funds, the availability of time. While the revitalization design is to compile the components of Lesson Study implementation and the need to present a third party as a change agent (Social Agent).